Analisis Rantai Pasok Melon Eksklusif PT Kebun Bumi Lestari (The Farmhill) di Wilayah Semarang : Exclusive Melon Supply Chain Analysis of PT Kebun Bumi Lestari (The Farmhill) in The Semarang Region - Yani Winda Sari Simanihuruk (Universitas Widya Gama Mahakam, 2021)
This study aimed to analyze trends demand, supply chain performance, supply chain flows and S-C-P (structure-conduct-performance. Research was conducted in July - August 2020 at PT Kebun Bumi Lestari (The Farmhill). The research method used survey with a total of 30 respondents, i.e. 5 suppliers, 15 producers, 5 retailers, and 5 consumers. The samples were determined using accidental sampling for consumers and snowball sampling for other chains. Data was analyzed using time series analysis for forecasting, margins and marketing efficiency analysis for supply chain performance, supply chain flow with flow of goods, finance and information, and the S-C-P approach. The result of forecast was the demand will increase in 2021, while the land area will decrease in 2021. Efficiency and marketing margins at producers and retail were 11% and 8%, Rp 13,500 and Rp 7,600, -. The flow of goods moved from upstream to downstream certainty, delivery on time, quality and quantity were fulfilled. Financial flows moved from downstream to upstream, with payments running as expected, information flows from upstream to downstream and vice versa in a transparent manner. The S-C-P approach for Structure, it was classified as oligopoly market with 40% market share. Conduct, selling rare and hydroponically grown products as a part of their product startegy, price strategy with reference to competitive pricing, general business conditions, quality, production costs, purchasing power, and demand. Promotion strategies, i.e. direct marketing, sales promotion, personal selling. Performance, marketing margin was efficient and profit ratio more than 1.